2018
DOI: 10.17240/aibuefd.2018.18.41844-444422
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi̇ Eği̇ti̇m Öğretmenleri̇ni̇n Kaynaştirma Eği̇ti̇mi̇nde Öz-Yeterli̇k Algilari Ve Hi̇zmeti̇çi̇ Eği̇ti̇m Gereksi̇ni̇mleri̇: Bi̇r Karma Yöntem Çalişmasi

Abstract: Karma yöntemle desenlenen bu çalışmada okul öncesi eğitim öğretmenlerinin kaynaştırma eğitiminde öz-yeterlik algıları ile kaynaştırma eğitimi öz-yeterlikleri ve hizmetiçi eğitim gereksinimlerine yönelik görüşlerini belirlemek amaçlanmıştır. Çalışma verileri yakınsayan paralel desen (NİC+NİT) kullanılarak toplanmıştır. Çalışmanın nicel boyutu 475, nitel boyutu ise 17 katılımcı ile yürütülmüştür. Araştırma verileri "Özel Gereksinimli Çocukların Kaynaştırılmasına Yönelik Öğretmen Yeterliği" ölçeği ve "Odak Grup G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Unlike these studies, inclusive education self-efficacy perceptions of preschool teachers were found to be at the levels of "above average" (Özsırkıntı, 2018), 'sufficient' (Sönmez et al, 2018), and 'with high probability' (Özokçu, 2018c). On the other hand, in the study of Sönmez et al (2018), it was concluded that preschool education teachers whom they interviewed in the qualitative aspect of the study found themselves inadequate. Similarly, in other studies conducted with preschool education teachers, teachers stated that they had lack of knowledge (Altun & Gülben, 2009;Artan & Uyanık-Balat, 2003;Aydın & Tuğluk, 2020;Gezer & Aksoy, 2019;Gök & Erbaş, 2011;Güleç-Aslan, 2020;Koçyiğit, 2015;Küçük-Doğaroğlu & Bapoğlu-Dümenci, 2015;Özdemir & Ahmetoğlu, 2012;Sucuoğlu et al, 2013;Yıkmış et al, 2018;Zabeli & Gjelaj, 2020).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Unlike these studies, inclusive education self-efficacy perceptions of preschool teachers were found to be at the levels of "above average" (Özsırkıntı, 2018), 'sufficient' (Sönmez et al, 2018), and 'with high probability' (Özokçu, 2018c). On the other hand, in the study of Sönmez et al (2018), it was concluded that preschool education teachers whom they interviewed in the qualitative aspect of the study found themselves inadequate. Similarly, in other studies conducted with preschool education teachers, teachers stated that they had lack of knowledge (Altun & Gülben, 2009;Artan & Uyanık-Balat, 2003;Aydın & Tuğluk, 2020;Gezer & Aksoy, 2019;Gök & Erbaş, 2011;Güleç-Aslan, 2020;Koçyiğit, 2015;Küçük-Doğaroğlu & Bapoğlu-Dümenci, 2015;Özdemir & Ahmetoğlu, 2012;Sucuoğlu et al, 2013;Yıkmış et al, 2018;Zabeli & Gjelaj, 2020).…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, in two studies conducted with preschool education teachers, inclusive self-efficacy perceptions of teachers were found to be at 'moderate' level (Çalışkan, 2019;Yaman, 2019). Unlike these studies, inclusive education self-efficacy perceptions of preschool teachers were found to be at the levels of "above average" (Özsırkıntı, 2018), 'sufficient' (Sönmez et al, 2018), and 'with high probability' (Özokçu, 2018c). On the other hand, in the study of Sönmez et al (2018), it was concluded that preschool education teachers whom they interviewed in the qualitative aspect of the study found themselves inadequate.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Each study focuses on the problems that contain different sample groups related to the subject. In the study of Sönmez, Alptekin and Bıçak (2018), different results were obtained after the analysis of quantitative and qualitative data in the study of preschool teachers' perceptions of self-efficacy and in-service training requirements in inclusive education with mixed method. In the quantitative dimension of the study, it was concluded that teachers found themselves competent in mainstreaming education, and in the qualitative dimension, teachers found themselves insufficient in mainstreaming education, and they needed in-service support.…”
Section: Introductionmentioning
confidence: 99%